The Value of Ultrasonography in The Diagnosis and Evaluation of Early Therapeutic Response of Cervical Tuberculous Lymphadenitis - Zeki Radhi, Sarab M.; Al-Nakib, Lamia H.; Gabash, Khairallah Muzhir (Journal of Baghdad College of Dentistry, 2017)
ABSTRACTBackground: Tuberculosis is a worldwide infectious disease in spite of advancement in health care system. Tuberculous lymphadenitis is the most prevalent form of extra pulmonary tuberculosis with predilection of cervical lymph nodes.Objectives: To evaluate the reliability of grey scale ultrasonography together with color Doppler in the diagnosis of cervical tuberculous lymph adenitis and evaluation of early therapeutic response.Subjects and methods:From July 2015 to May 2016 in Al-Karama teaching hospital /Kut city- Wasit-Iraq, 25 patients (14 males and 11 females) with ages range from (6-50) years. Ultrasonography examination was done for all patients and grey scale criteria (distribution, size, shape, echogenicity, echogenic hilum, intranodal necrosis and ancillary features) and vascular distribution were recorded to help in tuberculous lymphadenitis diagnosis. Excisional biopsy was done to confirm the diagnosis histopathologically. After chemotherapy the Patients were followed up after 46 days of treatment, again the grey scale criteria were recorded and compared with the 1st reading.Results: Ultrasonography could identify 88% of the patients (22/25) as having cervical tuberculous lymphadenitis while histopathology proved that only 80% of patients really have the disease. This mean that ultrasonography had good sensitivity (100%), specificity (60%) and accuracy (90%) with no false negative and 8% false positive.In following up the patients, grey scale ultrasonography criteria showed a significant difference for the same patients before and after 46 days of treatment.Conclusions: Ultrasonography was found to play a paramount role in detection, localization and delineation of cervical tuberculous lymph nodes hence grey scale and color Doppler are reliable in diagnosis of the disease and the evaluation of therapeutic response of the patients.